Large-eddy simulation of circular jet mixing: Lip- and inner-ribbed nozzles. (30th May 2018) - He, Chuangxin; Liu, Yingzheng; Yavuzkurt, Savas
Highlights: Influence of lip- and inner-ribbed nozzles on jet preferred modes are studied. Perfect agreements of LES with PIV and LIF measurements have established. Inner-ribbed jet has rapid decay of concentration and fast lateral spreading. Inner rib induces large structures at nozzle exit for good jet mixing. Inner rib enhances jet preferred modes with azimuthal wavenumber 1 and 2. Abstract: Jet mixing of a circular nozzle in two different configurations is extensively investigated using large-eddy simulation (LES), i.e., the lip-ribbed one with an annular rib at the nozzle exit, and the inner-ribbed one with a rib placed 1.0 D upstream of the nozzle exit; the latter one is particularly selected to generate unsteady reattachment of the separated shear layer near the nozzle exit. A jet issuing from a hydrodynamically smooth pipe with fully developed turbulent flow into a larger cylindrical domain (a 'pipe jet') is used as the baseline configuration for comparison. The Reynolds number based on the mean (bulk) velocity in the pipe and the pipe diameter is 6000. Validation of the LES approach is performed on the baseline pipe jet using particle image velocimetry (PIV) and laser-induced fluorescence (LIF) measurements; perfect agreement is obtained in terms of the mean streamwise velocity and concentration and their fluctuation parts. The LES results show that both ribbed jet configurations exhibit higher levels of mixing than the pipe jet; the most rapid decay of the centreline concentration and the largest entrainment are observed in the inner-ribbed jet. The inner-ribbed nozzle induced high flow fluctuations behind the rib due to frequent reattachment of flow to the pipe wall that are similar to what is known as fluid flapping motion. These flapping motions give rise to the energetic large-scale structures at the pipe exit and serve as an effective control imposed on the jet. The 'slice' proper orthogonal decomposition analysis performed on the flow helps to identify the jet's 'preferred modes' by selecting the most energetic structures with a specified azimuthal wavenumber. In the lip-ribbed jet, the separated shear layer modified the frequencies of the axisymmetric mode but made a limited contribution to the energy level of the jet preferred mode. In the inner-ribbed jet, however, the jet preferred modes were extensively altered. The single- and double-helical modes ( m = 1 and 2) were substantially intensified, with increasing energy levels up to 58%, giving rise to the significant enhancement of jet mixing, especially in the upstream regions.